2008
DOI: 10.1007/s00208-008-0224-5
|View full text |Cite
|
Sign up to set email alerts
|

Invariants of knot diagrams

Abstract: We construct a new order 1 invariant for knot diagrams. We use it to determine the minimal number of Reidemeister moves needed to pass between certain pairs of knot diagrams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…In [5] it is shown that the change in the value of I lk resulting from a Reidemeister move has one of the following forms:…”
Section: The Diagramsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [5] it is shown that the change in the value of I lk resulting from a Reidemeister move has one of the following forms:…”
Section: The Diagramsmentioning
confidence: 99%
“…We recall the definition of the invariant of knot diagrams in S 2 introduced in [5]. We denote the set of all knot diagrams in S 2 by D and the set of all two component links in R 3 by L. Given a knot diagram D ∈ D and a crossing a in D, define D a ∈ L to be the two-component link obtained by smoothing the crossing a (respecting the orientation of the strands).…”
Section: The Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…We let b i denote σ This theorem can also be obtained by using Arnold invariants. Hass and Nowik showed in section 4 in [6] that any lower bound of the number of Reidemeister moves between two knot diagrams obtained from the cowrithe coincides with that from the sum of adequately normalized Arnold invariants St + J + /2 of the underlying spherical closed curve.…”
Section: Arnold Introduced Three Invariants St Jmentioning
confidence: 96%
“…In [3], Carter, Elhamdadi, Saito and Satoh gave a lower bound for the number of RIII moves by using extended n-colorings of knot diagrams in R 2 . Hass and Nowik introduced a certain knot diagram invariant by using smoothing and linking numbers in [6], and gave in [7] an example of an infinite sequence of diagrams of the trivial knot such that the n-th one has 7n − 1 crossings, can be unknotted by 2n…”
Section: Arnold Introduced Three Invariants St Jmentioning
confidence: 99%